Missed opportunities for vaccination in health facilities in Swaziland - DALY, A. D; NXUMALO, M. P; BIELLIK, R. J (South African medical journal, 2003)
To determine whether potential exists to increase vaccination coverage in Swaziland by reducing missed opportunities. The standard World Health Organisation Expanded Programme on Immunisation (WHO EPI) protocol for assessing missed opportunities for vaccination was used to conduct this study. It involved client exit interviews and review of health cards. Selected variety of health facilities in Swaziland. Children less than 2 years of age and women of child-bearing age exiting each facility. Children and women eligible for vaccination exiting sampled health facilities. Fifty-four per cent of eligible children less than 2 years of age were missed for vaccination. This constitutes 26% of all children less than 2 years old leaving the facilities studied. Almost 100% of eligible women of childbearing age were missed for vaccination, constituting 88% of women leaving the study facilities. The distribution of the proportion of missed opportunities varied considerably between regions and health facility types. Missed opportunities occurred more frequently among those children requiring the first dose of all antigens and this may be linked to the high proportion of children missed for vaccination who did not possess a health card. Missed opportunities were more likely to occur in facilities providing integrated services. The frequent attendance at health facilities of the target group presents a valuable opportunity to increase vaccination coverage through avoidance of missed opportunities. All regions need to set vaccination coverage targets and develop plans to increase coverage, which should include strategies to ensure that all health workers routinely screen all clients for eligibility and vaccinate as required.